Comparative efficacy of Crotalaria juncea, Sorghum sudanense, and Trichoderma harzianum for managing Meloidogyne incognita and improving soil health under high root-knot nematode pressure - Ana García-Velázquez; Antonio Archidona-Yuste; Victoria Moreira; Álvaro López-García; Nuria Ferrol; Pablo Castillo; Juan Emilio Palomares-Rius (Crop Protection, 2026)

A conceptual framework for mineral supply chain traceability: Enabling conditions and core dimensions - Paulina Fernández; Michael Tost; Daniel Monfort Climent; Thania Nowaz; Emilio Castillo (The Extractive Industries and Society, 2026)

Environmental and Health Characterization of the Upper Atoyac River Basin, Puebla–Tlaxcala, Mexico - Regina Montero-Montoya; Leticia Yáñez-Estrada; Ofelia Morton-Bermea; Rocío López-Vargas; Karen Suárez-Larios; Gabriela Pérez-Castresana; Elizabeth Hernández-Álvarez; Rebeca Mejía-Saucedo; Ana Cervantes-Gloria; Luis Serrano-García; Alejandra Méndez-Serrano; Emilio Muñoz-Berruecos; et al. (Exposure and Health, 2026)

LA-COMET group: In vivo application of the comet assay in animal and plant models, including wild species - Gisela L. Poletta; Patricia Mussali-Galante; J. Alfredo Castillo-Ipiña; Guillermo Espinosa-Reyes; Ana Rosa Flores-Márquez; Donaji J. González-Mille; César A. Ilizaliturri-Hernández; Celeste Ruiz de Arcaute; Efraín Tovar-Sánchez; Juliana da Silva; Deidamia Franco; Ana Leticia García; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Mining in the lithium triangle: A multifaceted approach towards resource development in the face of climate, governance, and socio-environmental challenges - Camila Reyes; Emilio Castillo; Luis Felipe Orellana; Irene Del Real (The Extractive Industries and Society, 2025)

Body mass index and prognosis of infective endocarditis - Raquel Frías-García; Patricia Muñoz García; Marina Machado Vilchez; Gregorio Cuerpo Caballero; Raquel Rodríguez-García; M Ángeles Rodríguez-Esteban; M Carmen Fariñas-Álvarez; José M. Miró Meda; Andrea Gutiérrez Villanueva; Guillermo Ojeda-Burgos; Ane Josune Goikoetxea-Agirre; Marina Bernal Palacios; et al. (Infectious Diseases, 2025)

Bovine oocyte vitrification and recovery with ethylene glycol and either propylene glycol or dimethyl sulfoxide - Ashlyn Brewer; Emily Girka; Ashton Dalton; Emilio Gutierrez-Castillo; Kenneth R. Bondioli (Theriogenology, 2025)

Characterization of Surface and Bottom Longline Artisanal Shark Fisheries in the Northern Gulf of Tehuantepec, Mexico - Cristina Celaya-Castillo; Emilio I. Romero-Berny; Felipe Galván-Magaña; Jesús M. López-Vila; Wilfredo A. Matamoros (Thalassas: An International Journal of Marine Sciences, 2025)

Modeling and scenario building for climate change adaptation planning: The case of large mining in Chile - Rodrigo Jiliberto Herrera; Rodrigo Ramos-Jiliberto; Emilio Castillo Dintrans; Angel Allendes Caro; Luis Felipe Orellana Espinoza; Marco Billi; Marcelo Ramírez Valenzuela (Environmental Development, 2024)

Product differentiation in mineral commodities based on sustainability indicators: The case of copper mining - José I. Recabarren; Emilio Castillo; Andreína García; Jorge Cantallopts (Journal of Cleaner Production, 2024)

Looking for the surviving optimal areas for the threatened species Pinna nobilis in a highly anthropized coastal lagoon (Mar Menor, SE Spain) - Pilar Martínez-Martínez; Francisco Alonso-Sarría; Francisco Gomariz-Castillo; Enrique Reñé-Sánchez; Emilio Cortés-Melendreras; Yolanda Fernández-Torquemada; Francisca Giménez-Casalduero (Ocean & Coastal Management, 2024)

Drivers of Arbuscular Mycorrhizal Fungal Diversity Across 1,000 km of Chilean Vineyards - Paula Aguilera; Patricia Silva-Flores; Felipe Gaínza-Cortés; Claudio Pastenes; Claudia Castillo; Fernando Borie; Emilio Jorquera-Fontena; Claudio Inostroza-Blancheteau; Javier Retamal; César Marín (Journal of Soil Science and Plant Nutrition, 2024)

Perception of photovoltaic energy consumption in the Spanish primary sector. An environmentally profitable alternative - Francisco José Castillo-Díaz; Luis J. Belmonte-Ureña; Emilio Abad-Segura; Francisco Camacho-Ferre (Journal of Environmental Management, 2024)

New records, and molecular detection of vector-borne pathogens in Felicola subrostratus from eastern Mexico - Sokani Sánchez-Montes; Emilio Rendón-Franco; Claudia Irais Muñoz-García; Norma Edith Chagoya-Flores; María de los Ángeles Onofre-de Jesús; Jorge Luis Chagoya-Fuentes; José L. Bravo-Ramos; Marlene Solís-Cortés; Juan José Lara-Castillo; Ingeborg Becker; Gerardo G. Ballados-González (Veterinary Research Communications, 2023)

Valorizing industrial side streams through microalgae cultivation: A roadmap for process scale-up - Sandra Beatriz Castillo Castañeda; Rafael Emilio Altamirano Torres; Miguel Ángel Domínguez Vizcaíno; Elda M. Melchor-Martínez; Mariel Araceli Oyervides-Muñoz; Juan Eduardo Sosa Hernandez; Roberto Parra-Saldívar; Thomas Bisgaard; Omid Tavakoli; Irini Angelidaki; Solange I. Mussatto; Eduardo Krebs Kleingesinds; et al. (Algal Research, 2023)

Effect of bovine oocyte vitrification with EGTA and post-warming recovery with resveratrol on meiotic spindle, mitochondrial function, reactive oxygen species, and developmental competence - Emilio Gutierrez-Castillo; Fabian A. Diaz; Sydney A. Talbot; Kenneth R. Bondioli (Theriogenology, 2023)

New alien and native Ektaphelenchid nematodes (Tylenchomorpha: Ektaphelenchinae) from China with details on host association and geographical distribution - Jianfeng Gu; Maria Munawar; Juan Emilio Palomares-Rius; Pablo Castillo (European Journal of Plant Pathology, 2021)

Behind the Scenes for the Designation of the Corales de Profundidad National Natural Park of Colombia - David Alonso; Martha Vides-Casado; Francisco Arias-Isaza; Hernando Zambrano; Emilio Rodriguez; Venus Rocha-Gutierrez; Pilar Herron; Anny Castillo (Frontiers in Marine Science, 2021)
Deep-water environments make up 64% of the world’s oceans (nearly 202 million km 2 ). In the past, the belief that this environment represented one of the most stable and unproductive ecosystems on the planet has been refuted by scientific research and the interest of potential productive sectors evaluating seabed resources. Human activities that threaten the health of deep-sea threats are uncontrolled and unregulated fishing, deep-sea mining, oil spills, marine litter, and climate change. With recent advances in technology, the study of deep-sea coral communities is a growing subject. The deep-sea corals are long-lived, slow-growing, and fragile systems, making them especially vulnerable to physical damage. In the last 40 years, Colombia has discovered these communities’ existence scarcely distributed in its territorial waters. A representative and irreplaceable sample of deep-sea coral formations triggered in 2013 the establishment of the Corales de Profundidad National Natural Park, a Marine Protected Area (MPA), which holds 40% of the marine biodiversity known in the Colombian Caribbean continental shelf-slope break. The MPA’s essential ecological value is the Madracis myriaster species’ presence as a primary habitat-forming organism, a unique habitat for the Caribbean and the world. Here we describe the MPA creation process in three phases. Firstly, in the provisioning phase, three main threats from human activities are identified. Secondly, in the preparation phase, the area’s conservation objectives and management category are defined, and the negotiation process with the fishing, communications, and oil and gas economic sectors is described. Lastly, in the designation phase, three MPA scenario proposals were evaluated, assessing the minimum distance, the possible effects of activities in the area as the main criteria for the buffer zone and the management of possible future impacts. As a result, the most extended boundary was adopted, guaranteeing these communities’ conservation despite the limited information to carry out a complete planning process. The MPA designation is considered the first experience of deep communities in the Southern Caribbean and an example that it is possible to have effective conservation agreements with economic sectors.

Atacama Database: a platform of the microbiome of the Atacama Desert - Carolina A. Contador; Luis Veas-Castillo; Emilio Tapia; Marcela Antipán; Noemi Miranda; Benjamín Ruiz-Tagle; Jonathan García-Araya; Barbara A. Andrews; Mauricio Marin; Cristina Dorador; Juan A. Asenjo (Antonie van Leeuwenhoek, 2020)

Obesity Paradox in Ischemic Stroke: Clinical and Molecular Insights - Emilio Rodríguez-Castro; Manuel Rodríguez-Yáñez; Susana Arias-Rivas; María Santamaría-Cadavid; Iria López-Dequidt; Pablo Hervella; Miguel López; Francisco Campos; Tomás Sobrino; José Castillo (Translational Stroke Research, 2019)

Worse Outcome in Stroke Patients Treated with rt-PA Without Early Reperfusion: Associated Factors - Ramón Iglesias-Rey; Manuel Rodríguez-Yáñez; Emilio Rodríguez-Castro; José Manuel Pumar; Susana Arias; María Santamaría; Iria López-Dequidt; Pablo Hervella; Clara Correa-Paz; Tomás Sobrino; Denis Vivien; Francisco Campos; et al. (Translational Stroke Research, 2018)

Autonomous 3D metric reconstruction from uncalibrated aerial images captured from UAVs - Sebastián Castillo-Carrión; Jose-Emilio Guerrero-Ginel (International Journal of Remote Sensing, 2017)

Drug-related mortality among inpatients: a retrospective observational study - Alfredo José Pardo Cabello; Esperanza Del Pozo Gavilán; Francisco Javier Gómez Jiménez; Carmen Mota Rodríguez; Juan de Dios Luna Del Castillo; Emilio Puche Cañas (European Journal of Clinical Pharmacology, 2016)

Seasonality and anomalies of sea surface temperature off the coast of Nayarit, Mexico - Emilio Palacios-Hernández; Laura E. Carrillo; Anatoliy Filonov; Luis Brito-Castillo; Carlos E. Cabrera-Ramos (Ocean Dynamics, 2010)